Trust-based patterns for the management of inter-enterprises collaborations in context of extended enterprise. Issue 3 (2015) - Belkadi, F.; Bernard, A.
Abstract: Inter-enterprises collaboration became a big challenge in the new vision of industry of the future. Managers need to develop new collaborations to face several economic constraints. On one hand, it is necessary for an OEM to supply some activities in order to concentrate its effort on the activities providing real added value and competitive advantage. On another hand, companies need to bring their competencies and resources to propose innovative solution for specific markets. This paper presents a conceptual framework for supporting the management of collaborative situations. Based on the concept of trust level, this framework proposes a classification of different collaboration modes to be adopted in various contexts of inter-enterprises relationship. The implementation of such kinds of collaboration modes is achieved through several recommendations on process modelling and IT systems definition.